2022
DOI: 10.25124/jmi.v21i3.2791
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TQM Practice in Improving Business Performance’s Pharmaceutical Industry in Indonesia

Abstract: The primary purpose of this study is to investigate the role of Total Quality Management (TQM) on business performance in various dimensions. This study proposes a conceptual model that intends to study several research hypotheses. The data were obtained through an online questionnaire, sent to pharmaceutical companies manufactured generic products in Indonesia. The study was conducted based on responses received from 168 valid questionnaires, and it was used partial least squares structural equation modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…Previous study of Fitriyani et al (2021) aligns with this result as they determined causal relationship between TQM practices and the four perspectives of the BSC where TML had the highest level of influence.…”
Section: Inferential Analyses Of the Effect Of Qms Practices On Inter...supporting
confidence: 62%
“…Previous study of Fitriyani et al (2021) aligns with this result as they determined causal relationship between TQM practices and the four perspectives of the BSC where TML had the highest level of influence.…”
Section: Inferential Analyses Of the Effect Of Qms Practices On Inter...supporting
confidence: 62%
“…On the other hand, extra-role contextual performance is equally important as it fosters a positive work environment, promotes teamwork, enhances communication, and motivates employees to go beyond their prescribed duties to contribute to the organization's success (Sriboonlue & Puangpronpitag, 2019;Tjiptono, 2015). Such positive behaviors can lead to increased customer satisfaction, higher employee engagement and retention, better decision-making, and a competitive edge in the market, ultimately leading to improved business performance (Fitriyani et al, 2022;Nugraha et al, 2021). Moreover, employees' innovative behavior can also impact business performance positively, as it leads to the creation of new and better products and services, and enhances the organization's ability to adapt to changing market conditions (Detnakarin & Rurkkhum, 2019;Rahman et al, 2021).…”
Section: B Innovative Work Behavior and Business Performancementioning
confidence: 99%
“…Innovative employees who recognize problems and generate solutions or ideas and produce prototypes for mass production can increase a firm's profitability, sales, and market share (Mielniczuk & Laguna, 2020). Empirical studies have demonstrated a positive relationship between innovative behavior, competitiveness, and business performance, highlighting the importance of fostering innovative behavior among employees to achieve optimal business performance (Fitriyani et al, 2022;Park, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3, No. 3, September 2023 orang-orang di sekitarnya, mengambil nasihat dari mereka, dan berusaha mencapai mufakat (Imanuddin, et al, 2022). Kerendahan hati dalam kepemimpinan juga dianggap penting oleh Ibnu Ashur, yang berarti bahwa seorang pemimpin tidak boleh sombong atau berlaku tirani terhadap pengikutnya.…”
Section: Metode Penelitianunclassified